System for improving activity of lead-zinc tailings
Through grinding, microwave activation and ultrafine grinding systems, lead-zinc tailings are processed, and industrial flue gas exhaust is used for mineralization and drying, which solves the problems of low resource rate and high risk of heavy metals in the existing technology, and achieves high efficiency and greenness Resource utilization and environmental protection of lead and zinc tailings.
Patent Information
- Application Number
- CN202421173471.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2034-05-27
AI Technical Summary
The existing lead-zinc tailings treatment systems have low resource rate, high risk of heavy metals, low processing efficiency and long processing cycle, making it difficult to achieve green and environmentally friendly large-scale building materials utilization.
A system including grinding, microwave activation and ultrafine grinding was designed to coarsely crush and mineralize the industrial flue gas exhaust, use microwave activation and ultrafine grinding to improve the activity of lead-zinc tailings, and dry it through a fan and Mineralization, achieve resource utilization and reduce the risk of heavy metals.
The treatment cycle of lead-zinc tailings has been shortened, the resource utilization rate has been improved, the gelability and activity of tailings fine powder has been enhanced, environmental risks have been reduced, and the utilization of sustainable green building materials has been achieved.
Smart Images

Figure CN222362048U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of solid waste resource utilization, in particular to a system for improving the activity of lead-zinc tailings. Background Art
[0002] The existing lead-zinc tailings treatment system has the disadvantages of low resource utilization rate and high heavy metal risk. Therefore, a tailings treatment device with high treatment efficiency, short treatment cycle and green environmental protection is the key to solving the lead-zinc tailings disposal problem and laying the foundation for the large-scale utilization of building materials. Utility Model Content
[0003] In order to solve the above problems, the purpose of the utility model is to provide a green, environmentally friendly, resource-saving efficient and short-processing period lead-zinc tailings treatment system. Through this system, lead-zinc tailings micro powder with high activity, good gelling property and excellent resource utilization in the field of building materials can be obtained.
[0004] To achieve the above purpose, the utility model proposes a system for improving the activity of lead-zinc tailings, comprising:
[0005] Tailings dump (1), first conveying device (2), grinding device (3), second conveying device (4), microwave activation device (5), third conveying device (6), ultrafine grinding device (7), second mineralization device (8), activator storage tank (9), fifth conveying device (10), first mineralization device (11), third fan (12), chimney (13), fourth fan (14), first fan (15), second fan (16), fourth conveying device (17), product silo (18);
[0006] The outlet of the tailings dump (1) is connected to the inlet of the first conveying device (2), and the outlet of the first conveying device (2) is connected to the inlet of the grinding device (3); one side of the grinding device (3) is connected to the inlet of the first mineralization device (11), and the other side is connected to the outlet of the first fan (15); one side of the outlet of the first mineralization device (11) is connected to the inlet of the second conveying device (4), and the other side of the outlet is connected to the inlet of the third fan (12), and the outlet of the third fan (12) is connected to the chimney (13); the outlet of the second conveying device (4) is connected to the inlet of the microwave activation device (5), the outlet of the microwave activation device (5) is connected to the inlet of the third conveying device (6), and the outlet of the third conveying device (6) is connected to the The outlet of the activator storage tank (9) is connected to the inlet of the fifth conveying device (10), and the outlet of the fifth conveying device (10) is connected to the inlet of the other side of the ultrafine grinding device (7); the outlet of the ultrafine grinding device (7) is connected to the inlet of one side of the second mineralization device (8), the outlet of the second fan (16) is connected to the inlet of the other side of the second mineralization device (8), the outlet of the second mineralization device (8) is connected to the inlet of the fourth fan (14), and the outlet of the fourth fan (14) is connected to the inlet of the chimney (13); the outlet of the other side of the second mineralization device (8) is connected to the inlet of the fourth conveying device (17), and the outlet of the fourth conveying device (17) is connected to the inlet of the product silo (18);
[0007] The inlets of the first fan (15) and the second fan (16) are connected to industrial flue gas and tail gas.
[0008] The system in the utility model uses a grinding device and a fan to blow industrial flue gas to coarsely crush and mineralize the lead-zinc tailings, performs the first activation in a microwave activation device, and then realizes the secondary activation through an ultrafine grinding device, which not only shortens the processing cycle of the lead-zinc tailings, but also lays the foundation for the subsequent large-scale utilization and improvement of the resource utilization rate of the activated lead-zinc tailings. The grinding device and the ultrafine grinding device are connected to the fan, and the fan is used to blow hot flue gas to dry and mineralize the lead-zinc tailings, and then the mineralized tail gas is discharged through the fan, which can not only activate the lead-zinc tailings, but also achieve the reuse of flue gas, so that it can meet the emission standards, improve resource utilization and is also beneficial to environmental protection, and achieve sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 It is the XRD spectrum of the lead-zinc tailings in the utility model;
[0010] Figure 2 This is a system flow chart for improving the activity of lead-zinc tailings in Example 1 of the utility model;
[0011] Figure 3 It is an electron microscope image of the unactivated lead-zinc tailings in the utility model;
[0012] Figure 4 This is an electron microscope image of the tailings powder after activation in Example 2 of the utility model. DETAILED DESCRIPTION
[0013] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limitations on the present invention. If specific techniques or conditions are not indicated in the embodiments, they are carried out according to the techniques or conditions described in the literature in this area or according to the product instructions. If the manufacturer is not indicated for the reagents or instruments used, they are all conventional products that can be obtained commercially. In the following embodiments, if not clearly stated, "%" refers to weight percentage.
[0014] The lead-zinc tailings used in the following examples are from a lead-zinc tailings plant in Jiangxi Province. Its chemical composition is shown in Table 1, and its mineral composition is shown in Table 1. Figure 1 shown.
[0015] Table 1 Lead-zinc tailings component analysis results (wt%)
[0016]
[0017]
[0018] Depend on Figure 1 From the results in Table 1, it can be seen that the SiO2 content of the lead-zinc tailings is 66.79%, which is a silicon-rich tailings. In addition, it also contains Al2O3, Fe3O4, PbO, ZnO and other substances. Its main mineral components are quartz, muscovite and hydrocalcium zeolite.
[0019] A method for improving the activity of lead-zinc tailings, comprising the steps of:
[0020] S1. Coarse crushing: coarsely crushing the lead-zinc tailings, using flue gas and tail gas to dry and achieve primary mineralization during the coarse crushing process to obtain the first tailings powder;
[0021] S2, primary activation: performing microwave activation on the first tailings powder obtained in step S1 to obtain a second tailings powder;
[0022] S3, secondary activation: adding an activator to the second tailings powder obtained in step S2, uniformly mixing, and then performing ultrafine grinding and secondary activation to obtain a third tailings powder;
[0023] S4, mineralized finished product: The third tailings powder is dried with flue gas and exhaust gas to achieve secondary mineralization, and finally the tailings fine powder finished product is obtained.
[0024] Preferably, the particle size of the first tailings powder is less than 100 mesh.
[0025] Preferably, the temperature of the flue gas in steps S1 and S4 is 90-200°C; more preferably, the temperature of the flue gas in steps S1 and S4 is 110-115°C.
[0026] Preferably, the power of microwave activation in step S2 is 600-900w; more preferably, the power of microwave activation in step S2 is 900w.
[0027] Preferably, the microwave activation time in step S2 is 10-50 min; more preferably, the microwave activation time in step S2 is 10-20 min.
[0028] Preferably, in step S3, the activator is graphene oxide.
[0029] Preferably, the amount of the activator added in step S3 is 0.02%-0.05% of the mass of the second tailings powder. More preferably, the amount of the activator added is 0.03%.
[0030] Preferably, the specific surface area of the third tailings powder in step S3 is >500m 2 / g.
[0031] The tailings powder obtained by the lead-zinc tailings activation system of the utility model is used to replace cement in concrete products or to prepare green building materials, and the addition mass ratio of the tailings powder is 20%-30%.
[0032] Example 1: A system for improving the activity of lead-zinc tailings
[0033] The system in this embodiment is set up based on the method for improving the activity of lead-zinc tailings in the above embodiment. The specific system is as follows Figure 2 As shown, Figure 2 This is a system flow chart for improving the activity of lead-zinc tailings in Example 1 of the utility model.
[0034] The lead-zinc tailings in the tailings yard (1) are transported to the grinding device (3) through the first conveying device (2), and the lead-zinc tailings are coarsely crushed in the grinding device (3) to obtain tailings powder with a particle size of less than 100 mesh. The industrial flue gas blows the tailings powder in the grinding device (3) into the first mineralization device (11) through the first fan (15), so that the tailings powder is dried by the industrial combustion flue gas during the coarse crushing process and primary mineralization is achieved. The tailings powder in the first mineralization device (11) is transported to the microwave activation device (5) through the second conveying device (4). The flue gas after primary mineralization is blown into the chimney (13) through the third fan (12), and the flue gas after mineralization can meet the emission standards.
[0035] Preferably, the first conveying device (2) is a belt conveyor; the grinding device (3) is a horizontal roller mill or a vertical mill; the first fan (15) and the third fan (12) are both flue gas fans; the first mineralizing device (11) is a bag filter; the second conveying device (4) is any one of a scraper conveyor, a bucket elevator, a pneumatic conveyor and a screw conveyor; and the chimney (13) is any one of a steel chimney, a brick-concrete chimney or a concrete chimney.
[0036] The tailing powder after primary mineralization is microwave activated in a microwave activation device (5), and the microwave activated tailing powder is transported to an ultrafine grinding device (7) via a third conveying device (6). At the same time, an activator is transported from an activator storage tank (9) to an ultrafine grinding device (7) via a fifth conveying device (10), and is ground and activated together with the microwave activated tailing powder to obtain a secondary activated tailing powder, wherein the tailing powder has a specific surface area of more than 500 m 2 / g.
[0037] Preferably, the microwave activation device (5) is a microwave irradiation belt conveyor or a drum microwave irradiation device; the third conveying device (6) is any one of a scraper conveyor, a bucket elevator, a pneumatic conveyor or a screw conveyor; the ultrafine grinding device (7) is a ball mill or a pneumatic crusher; the activator storage tank (9) is a steel silo; and the fifth conveying device (10) is a water pump.
[0038] Then, the tailings powder is subjected to secondary mineralization, and the industrial smoke exhaust gas is blown into the second mineralization device (8) through the second fan (16), the tailings powder is dried and secondary mineralized to obtain active tailings powder. After the secondary mineralization is completed, the smoke exhaust gas enters the chimney (13) through the fourth fan (14) and is discharged in compliance with the emission standards.
[0039] Preferably, the second fan (16) and the fourth fan (14) are both flue gas fans; and the second mineralization device (8) is a fluidized bed mineralization device with a bag dust removal device.
[0040] Finally, the active tailings powder is transported to the product silo (18) through the fourth transport device (17) and stored as a green building material raw material.
[0041] Preferably, the fourth conveying device (17) is any one of a scraper conveyor, a bucket elevator, a pneumatic conveyor or a screw conveyor; and the product silo (18) is a steel silo or a concrete silo.
[0042] Embodiment 2:
[0043] 1. Activation method of lead-zinc tailings:
[0044] S1. Coarse pulverization: The lead-zinc tailings are coarsely pulverized, and the coarse pulverization process uses industrial combustion flue gas to dry and achieve primary mineralization to obtain the first tailings powder. The particle size of the first tailings powder is <100 mesh, and the flue gas temperature is 130°C.
[0045] S2, primary activation: the first tailings powder obtained in step S1 is subjected to microwave activation to obtain a second tailings powder, the microwave activation power is 900 W, and the activation time is 10 min.
[0046] S3, secondary activation: Graphene oxide is added to the second tailings powder obtained in step S2, and the added ratio is 0.03% of the mass of the second tailings powder. After uniform mixing, ultrafine grinding is performed for secondary activation to obtain a third tailings powder. The ultrafine grinding is performed at 200r / min and co-ball milling for 60min. The specific surface area of the obtained third tailings powder is>500m 2 / g.
[0047] S4, mineralized finished product: The third tailings powder is dried with industrial combustion flue gas and secondary mineralized, the flue gas temperature is 130°C, and finally activated tailings powder is obtained.
[0048] 2. Performance verification experiment: A performance verification experiment was carried out on the tailings powder obtained in Example 2.
[0049] 1) Microstructure comparison
[0050] Figure 3 This is an electron microscope image of the unactivated lead-zinc tailings in the utility model. Figure 4 This is an electron microscope image of the activated tailings powder in Example 2 of the utility model. The unactivated tailings powder in this example is obtained by simple fine grinding. Figure 3 and Figure 4 It can be seen that compared with the unactivated tailings powder, the particle size of the activated tailings powder becomes smaller, and no obvious large particles appear. The specific surface area of the tailings powder activated by the utility model is>500m 2 / g, compared with simple fine grinding of tailings, the volume average particle size of the obtained micropowder under the same treatment conditions was reduced from 69.715μm to 67.305μm, and d(0.5) was reduced. Composite activation can make the overall particle size of lead-zinc tailings micropowder smaller.
[0051] 2) Activity and compressive strength test
[0052] According to the "Cement mortar strength test method" described in the national standard "Cement mortar strength test method (ISO method) G / T 17671-2021", the tailings fine powder obtained by the method in the utility model is used to replace 20wt% of the cement in the cement mortar.
[0053] The mass ratio of cement mortar is one part of cementitious material, three parts of Chinese ISO standard sand and half part of water, and 40mm×40mm×160mm prism cement mortar is made for compressive strength testing. Each pot of material requires 450g of cementitious material (including 90g of lead-zinc tailings, 360g of cement), 1350g of standard sand, and 225g of water to form three test blocks. After curing to the specified age, the compressive strength is tested according to the method specified in 10-Test Procedure in "Test Method for Strength of Cement Mortar (ISO Method) G / T 17671-2021", and its volcanic ash activity is determined, as shown in Table 2, which is a table of volcanic ash activity of the tailings powder obtained in Example 2 of the utility model.
[0054] The results in Table 2 show that compared with the unactivated tailings powder, the 7d activity index of the activated tailings powder increased from 64.44% to 84.22%, an increase of 19.78%; the 28d activity index increased from 61.15% to 81.97%, an increase of 20.82%. The main reason may be that the activation method in the utility model changes the particle size, specific surface area and other indicators of the lead-zinc tailings, the crystal structure is distorted, the crystallinity begins to decrease, and the lattice dislocation, defects, recrystallization and other phenomena gradually appear, destroying the structure of Si-O and Al-O in the lead-zinc tailings, showing solubility, forming an amorphous form coated on the surface of the particles and easily soluble in water, making it easier for water molecules to enter its interior, accelerating the hydration reaction, and then affecting the volcanic ash activity of the lead-zinc tailings. Therefore, the activated tailings powder in the utility model is easier to form CSH gel, so that its gelling property is improved, and cement mortar with higher compressive strength can be prepared.
[0055] Table 2 is the volcanic ash activity table of the tailings powder obtained in Example 2 of the utility model
[0056] sample 7d activity index 28d activity index Unactivated tailings powder 64.44% 61.15% Activated tailings powder 84.22% 81.97%
[0057] Table 3 is a table of compressive strength test results of tailings powder obtained in Example 2 of the present utility model. According to the results in Table 3, compared with unactivated tailings powder, the 7d compressive strength of cement mortar specimens prepared by adding activated tailings powder is increased from 21.1MPa to 31.5MPa, an increase of 49.29%; the 28d compressive strength is increased from 32.9MPa to 44.1MPa, an increase of 34.04%.
[0058] The main reason may be that the volcanic ash activity of the activated lead-zinc tailings increases. Compared with the unactivated tailings, when the activated lead-zinc tailings enter the hydration reaction, it will promote the hydration reaction process and increase the hydration products, thereby improving the compressive strength of the mortar specimen.
[0059] Table 3 is a table showing the compressive strength test results of the tailings powder obtained in Example 2 of the present utility model.
[0060] sample 7d compressive strength 28d compressive strength Unactivated tailings powder mortar specimen 21.1MPa 32.9MPa Activated tailings micro powder mortar specimen 31.5MPa 44.1MPa
[0061] 3) Concrete mechanical properties verification experiment
[0062] The activated tailings powder obtained in Example 2 and the unactivated tailings powder were used to replace 20wt% of cement in cement mortar to prepare concrete, and the concrete mix ratio was designed according to JTG / T 3650-2020 "Technical Specifications for Highway Bridge and Culvert Construction" and JTG / T3420-2020 "Test Procedure for Cement and Cement Concrete for Highway Engineering".
[0063] Each concrete requires 388kg / m 3 Cementitious materials (including cement 310.4kg / m 3 、Lead-zinc tailings 77.6kg / m 3 )、712kg / m 3 Fine aggregate, 1067kg / m 3 Coarse aggregate, 233kg / m 3 of water, plus 0.2% polycarboxylate water reducer. Pour the required materials into a concrete mixer and mix evenly, pour the resulting cement mortar into the specified mold, demold after 24 hours and cure to the specified age. According to the method specified in GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 7d compressive strength and 7d splitting tensile strength of concrete are tested, as shown in Table 4, which is a table of 7d compressive strength and splitting tensile strength test results when the activated tailings powder and the unactivated tailings powder of the utility model are added to concrete respectively.
[0064] The results in Table 4 show that compared with unactivated tailings powder, the 7d compressive strength of concrete specimens prepared by adding activated tailings powder increased from 16.7MPa to 6.2MPa, an increase of 37.13%; the 7d splitting tensile strength increased from 0.98MPa to 0.16MPa, an increase of 16.33%.
[0065] The reason may be that the volcanic ash activity of the activated tailings powder increases. Compared with the unactivated tailings powder, when the activated tailings powder enters the hydration reaction, it will promote the hydration reaction process and increase the hydration products, thereby improving the compressive strength and splitting strength of the concrete specimens.
[0066] Table 4 is a table showing the 7d compressive strength and splitting tensile strength test results of the activated tailings powder and the unactivated tailings powder respectively added to concrete.
[0067] sample 7d compressive strength 7d splitting tensile strength Unactivated tailings powder concrete 16.7MPa 0.98MPa Activated tailings powder concrete 22.9MPa 1.14MPa
[0068] 4) Comparison experiment of typical heavy metal lead and zinc BCR forms
[0069] Digestion of concrete with lead-zinc tailings before and after activation:
[0070] S4.1. Accurately weigh 0.100 g of the activated tailings powder and the unactivated tailings powder obtained in Example 2 and add them into a polytetrafluoroethylene digestion tube, and then add 5 mL of hydrofluoric acid, 3 mL of perchloric acid and 3 mL of nitric acid in sequence;
[0071] S4.2 Tighten the digestion tube and seal it in the matching graphite digestion instrument. Set the digestion temperature to 190℃, the digestion time to 5h, the acid removal temperature to 160℃, and the acid removal time to 5h;
[0072] S4.3 After the digestion is complete, filter the digestion solution with a 0.22 μm water-based nylon filter and dilute to 50 mL with 2% HNO3 to obtain the test solution.
[0073] Heavy metals were analyzed using the BCR continuous extraction method supported by the European Committee for Standardization and Analysis (The Community Bureau of Reference, Now the Standards, Measurements and Testing Programme). The BCR forms of heavy metals are mainly divided into weak acid extraction state (F1: exchangeable state and carbonate bound state), reducible state (F2: iron and manganese oxide bound state), oxidizable state (F3: organic matter and sulfide bound state) and residual state (F4).
[0074] Heavy metals in weak acid extractable state (F1) and reducible state (F2) are easily absorbed by plants, which has a negative impact on the ecological environment; the oxidizable state (F3) is the form of metal ions combined with organic matter and sulfide, which is insoluble in the form of sulfide ions and metal particles with organic active groups as ligands. When organic matter reacts under oxidizing conditions, some metals will be released. The residual solid contains solids that can mainly solidify the metal in the crystal structure, so the residual heavy metals are regarded as the most stable metal form; when the content of metal residual state (F4) in the sample increases, it indicates that it can exist more stably in the environment and is not easy to cause environmental risks.
[0075] Table 5 is a table of the BCR form content of lead in activated tailings powder and unactivated tailings powder concrete, and Table 6 is a table of the BCR form content of zinc in activated tailings powder and unactivated tailings powder concrete. The results of Tables 5 and 6 show that the activated tailings powder basically achieves the solidification and stabilization of metal lead and zinc. Comparing the BCR forms of lead and zinc in lead-zinc tailings before and after activation, it can be seen that the proportion of F4 state in lead and zinc in activated tailings powder concrete is higher than that in unactivated tailings powder concrete. Among them, for heavy metal zinc, the proportion of F4 state increased by 6%, which shows that the tailings activation method in the utility model has a certain solidification and stabilization effect on the heavy metals of the tailings powder added to the concrete, and can reduce the environmental risk of lead-zinc tailings as a substitute for cementitious materials. The tailings powder obtained by the activation method of the utility model can promote the hydration reaction and generate more hydration products. The cementitious material generated by the reaction can stabilize the heavy metal ions in its crystal structure through physical encapsulation and ion exchange, improve the solidification of heavy metals in concrete, and further reduce the ecological risks of lead-zinc tailings.
[0076] Table 5 shows the BCR content of lead in activated tailings powder and unactivated tailings powder concrete
[0077] lead F1 / % F2 / % F3 / % F4 / % Unactivated tailings powder concrete 0 1 1 98 Activated tailings powder concrete 0 0 1 99
[0078] Table 6 shows the BCR content of zinc in activated tailings powder and unactivated tailings powder concrete
[0079] Zinc F1 / % F2 / % F3 / % F4 / % Unactivated tailings powder concrete 0 34 19 47 Activated tailings powder concrete 0 32 15 53
[0080] Embodiment 3:
[0081] S1. Coarse pulverization: The lead-zinc tailings are coarsely pulverized, and the coarse pulverization process uses industrial combustion flue gas to dry and achieve primary mineralization to obtain the first tailings powder. The particle size of the first tailings powder is <100 mesh, and the flue gas temperature is 110°C.
[0082] S2, primary activation: the first tailings powder obtained in step S1 is subjected to microwave activation to obtain a second tailings powder, the microwave activation power is 600 W, and the activation time is 20 min.
[0083] S3, secondary activation: add graphene oxide to the second tailings powder obtained in step S2, the added ratio is 0.04% of the mass of the second tailings powder, and after uniform mixing, ultrafine grinding is performed for secondary activation to obtain a third tailings powder. Ultrafine grinding is performed at 200r / min and co-ball milling for 40min. The specific surface area of the obtained third tailings powder is>500m 2 / g.
[0084] S4, mineralized finished product: The third tailings powder is dried with industrial combustion flue gas and secondary mineralized, the flue gas temperature is 110°C, and finally activated tailings powder is obtained.
[0085] The parameters of the tailings powder obtained by the method in Example 3 are shown in Table 7. The surface binding energy of the tailings powder is low, and the lattice distortion of the silicon-oxygen tetrahedron is deepened, thereby improving the reactivity of the lead-zinc tailings. At the same time, the tailings powder obtained in Example 3 has the characteristics of small particle size and large specific surface area, high intensity activity index at 7d and 28d, and the four BCR forms of lead and zinc in the tailings powder are relatively uniform.
[0086] The tailings powder obtained in Example 3 was used to replace 20wt% of cement in cement mortar for concrete preparation. The concrete mix ratio was designed according to JTG / T3650-2020 "Technical Specifications for Highway Bridge and Culvert Construction" and JTG / T 3420-2020 "Test Procedures for Highway Engineering Cement and Cement Concrete"; the compressive strengths of the obtained tailings powder concrete at 7d and 28d were 20.4MPa and 28.6MPa, respectively, and the BCR forms of heavy metals lead and zinc in the concrete were mainly F4 states, accounting for 75% and 100%, respectively; the leaching concentrations of lead and zinc in the concrete were 0mg / L and 0.0079mg / L, respectively, and the tailings concrete achieved the solidification and stability of heavy metals, and the finished product had high environmental safety.
[0087] Table 7 is the tailings powder parameter table in Example 3
[0088]
[0089] Embodiment 4:
[0090] S1. Coarse pulverization: The lead-zinc tailings are coarsely pulverized, and the coarse pulverization process uses industrial combustion flue gas to dry and achieve primary mineralization to obtain the first tailings powder. The particle size of the first tailings powder is <100 mesh, and the flue gas temperature is 115°C.
[0091] S2, primary activation: the first tailings powder obtained in step S1 is subjected to microwave activation to obtain a second tailings powder, the microwave activation power is 900 W, and the activation time is 40 min.
[0092] S3, secondary activation: add graphene oxide to the second tailings powder obtained in step S2, the added ratio is 0.05% of the mass of the second tailings powder, and after uniform mixing, ultrafine grinding is performed for secondary activation to obtain the third tailings powder. The ultrafine grinding is performed at 200r / min and co-ball milling for 60min. The specific surface area of the obtained third tailings powder is>500m 2 / g.
[0093] S4, mineralized finished product: The third tailings powder is dried with industrial combustion flue gas and secondary mineralized, the flue gas temperature is 115°C, and finally activated tailings powder is obtained.
[0094] The parameters of the tailings powder obtained by the method in Example 4 are shown in Table 8. The surface binding energy of the tailings powder is low, and the lattice distortion of the silicon-oxygen tetrahedron is deepened, thereby improving the reactivity of the lead-zinc tailings. At the same time, the tailings powder obtained in Example 4 has the characteristics of small particle size and large specific surface area, high intensity activity index at 7d and 28d, and the four BCR forms of lead and zinc in the tailings powder are relatively uniform.
[0095] The tailings powder obtained by the method in Example 4 is used to replace 20wt% cement in cement mortar for concrete preparation. Concrete mix design is carried out according to JTG / T 3650-2020 "Technical Specifications for Highway Bridge and Culvert Construction" and JTG / T 3420-2020 "Test Procedures for Highway Engineering Cement and Cement Concrete"; the compressive strengths of the obtained tailings powder concrete at 7d and 28d are 21.8MPa and 30.1MPa, respectively, and the BCR forms of heavy metal lead and zinc in the tailings powder concrete are mainly F4 states, accounting for 76% and 100%, respectively, and the leaching concentrations of lead and zinc in the concrete are 0mg / L and 0.0086mg / L, respectively. The tailings powder concrete realizes the solidification and stability of heavy metals, and the finished product has high environmental safety.
[0096] Table 8 is the tailings powder parameter table in Example 4
[0097]
[0098]
[0099] Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are illustrative and cannot be understood as limitations on the present invention. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.
Claims
1. A system for improving the activity of lead-zinc tailings, characterized in that: include: Tailings dump (1), first conveying device (2), grinding device (3), second conveying device (4), microwave activation device (5), third conveying device (6), ultrafine grinding device (7), second mineralization device (8), activator storage tank (9), fifth conveying device (10), first mineralization device (11), third fan (12), chimney (13), fourth fan (14), first fan (15), second fan (16), fourth conveying device (17), product silo (18); The outlet of the tailings dump (1) is connected to the inlet of the first conveying device (2), and the outlet of the first conveying device (2) is connected to the inlet of the grinding device (3); one side of the grinding device (3) is connected to the inlet of the first mineralization device (11), and the other side is connected to the outlet of the first fan (15); one side of the outlet of the first mineralization device (11) is connected to the inlet of the second conveying device (4), and the other side of the outlet is connected to the inlet of the third fan (12), and the outlet of the third fan (12) is connected to the chimney (13); the outlet of the second conveying device (4) is connected to the inlet of the microwave activation device (5), the outlet of the microwave activation device (5) is connected to the inlet of the third conveying device (6), and the outlet of the third conveying device (6) is connected to the The outlet of the activator storage tank (9) is connected to the inlet of the fifth conveying device (10), and the outlet of the fifth conveying device (10) is connected to the inlet of the other side of the ultrafine grinding device (7); the outlet of the ultrafine grinding device (7) is connected to the inlet of one side of the second mineralization device (8), the outlet of the second fan (16) is connected to the inlet of the other side of the second mineralization device (8), the outlet of the second mineralization device (8) is connected to the inlet of the fourth fan (14), and the outlet of the fourth fan (14) is connected to the inlet of the chimney (13); the outlet of the other side of the second mineralization device (8) is connected to the inlet of the fourth conveying device (17), and the outlet of the fourth conveying device (17) is connected to the inlet of the product silo (18); The inlets of the first fan (15) and the second fan (16) are connected to industrial flue gas and tail gas.